Carbon Nanotube Forests: Engineering Carbon Nanotube Forest Superstructure for Robust Thermal Desalination Membranes (Adv. Funct. Mater. 36/2019). (3rd September 2019) - Sun, Meng; Boo, Chanhee; Shi, Wenbo; Rolf, Julianne; Shaulsky, Evyatar; Cheng, Wei; Plata, Desiree L.; Qu, Jiuhui; Elimelech, Menachem
Abstract : In article number 1903125, Menachem Elimelech and co‐workers develop a novel thermal desalination membrane via in situ engineering of a carbon nanotube forest (CNTF) superstructure on a porous nanofiber substrate. Precise design of the CNTF architecture endows the composite membrane with outstanding wetting resistance against both water and oil, stable water vapor flux, and near complete salt rejection (>99.9%).